The use of bioceramic root canal sealers for obturation of the root canal system. a review. - Mustaffa, Musliana (IIUM Press, 2021)
The use of bioceramic root canal sealers in endodontics is a promising approach because of the advantages such as improved flow properties, biocompatible and could promote the formation hard tissue. Due to the recent technology and limited scientific evidence, the effectiveness of bioceramic root canal sealers remains unclear. This article focuses on the physicochemical properties, biocompatibility, biomineralisation, retreatability, 3D obturation and current practice of using bioceramic root canal sealers. The relevant articles for this review were searched manually from Google Scholar and PubMed using keywords ‘bioceramic root filling material AND endodontics’, ‘bioceramic root canal sealers AND endodontics’, ‘cytotoxicity AND bioceramic root canal sealers’, ‘bioceramic root canal sealers AND physicochemical properties’, ‘biomineralisation AND bioceramic root canal sealers’ and ‘retreatment efficacy AND bioceramic root filling materials’. Since the clinical data concerning the obturation with bioceramic root canal sealers is lacking, the selection of materials should be made based on the available scientific evidence, individual cases, material availability and operator’s preference.